Correlates of wife abuse among ever married males in selected regions in the Philippines - Manalo, Maria Fidelis C. (2003)
We describe the marital, social-psychological, social-structural and social location factors associated with wife abuse among married men in selected regions in the Philippines, using data from the Reproductive Health Survey 2000. About eight percent (8.4%) of married men in our sample of 5,507 reported wife abuse. Getting married young and having a history of parental abuse emerge as strong predictors of domestic violence. Lower levels of education in women are associated with a higher likelihood of wife abuse. Income, employment status of the men and their spouse, occupational status discrepancy, and men's educational attainment, do not predict intimate partner violence. Men who object to their partner wanting to improve her education or visit her friends without them and who get their way during disagreements, are more likely to use physical violence. Men who, jointly with their wives or by themselves, usually decide on food matters, are also more likely to give in to wife abuse. Men who predominantly handle the household budget are more likely as well to beat their wives, though the association is not significant.
Thesis (MS Epidemiology, Public Health) -- University of the Philippines, Manila.
Keywords: Wife abuse; Abused wives